A solid-state battery electrolyte containing a nitrile-based fluorinated additive and a method of making the same

CN122889830APending Publication Date: 2026-10-09HUZHOU DEJIA ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611017550.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,本领域技术人员在深入的电化学机理研究中发现,常规的聚乙二醇二丙烯酸酯基原位交联固态电解质在微观层面依然存在极难克服的技术瓶颈

Benefits of technology

[0028]本发明在固态聚合物网络中极其严格地将2,2-二氟丙二腈中氰基与双锂盐中锂离子的摩尔比限定在0.15:1至0.4:1的微观区间内。2,2-二氟丙二腈分子受氟原子强吸电子诱导形成了极度缺电子中心,该中心能够与双锂盐中庞大的阴离子(如双三氟甲磺酰亚胺锂阴离子)产生强烈的偶极相互作用并将其牢牢锚定,同时其端基氰基的适度配位强行削弱了聚乙二醇二丙烯酸酯基体中醚氧键对锂离子的原生束缚,这种靶向重塑溶剂化鞘的微观机制极大释放了游离态锂离子,使得复合体系在室温下的锂离子迁移数实现了断崖式跃升;而传统的聚合物固态电解质受限于阴离子的高速游离和锂离子的缓慢传输,往往面临极其严重的浓差极化问题,本发明从分子热力学层面彻底打破了这一桎梏,不仅根除了大电流充放电时游离阴离子聚集引发的极化现象,更从源头上抑制了因空间电荷层失衡而诱发的锂枝晶形核与生长,为固态电池的高安全快充提供了坚实保障。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889830A_ABST
    Figure CN122889830A_ABST
Patent Text Reader

Abstract

The application discloses a solid-state battery electrolyte containing nitrile fluorinated compound additives and a preparation method thereof, and belongs to the technical field of lithium ion battery electrolyte. The electrolyte is formed by in-situ thermal polymerization and cross-linking of a liquid precursor, and the precursor mainly comprises polyethylene glycol diacrylate, a double lithium salt system, nanoscale lithium lanthanum zirconium oxygen and a 2,2-difluoropropylene dinitrile additive. The core lies in that the molar ratio of the cyano group in the 2,2-difluoropropylene dinitrile to lithium ions is 0.15:1-0.4:1, and the mass ratio of the additive to the nanoscale lithium lanthanum zirconium oxygen is 1:4-1:8. Through the synergism of the strong electron-withdrawing effect of the fluorine atom in the molecular structure and the above specific micro ratio, the application targets the remodeling of the solvation sheath, and realizes the single-molecular-level wetting of the inorganic filler interface. The application completely eliminates the micro-agglomeration of the nanoparticles, effectively inhibits the high-pressure side reaction, and significantly improves the lithium ion transference number, the critical current density and the high-pressure cycle stability of the solid-state electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery electrolyte technology, and more particularly to a solid-state battery electrolyte containing nitrile fluoride additives and its preparation method. Background Technology

[0002] With the rapid development of portable electronic devices and the new energy vehicle industry, the market has placed unprecedentedly stringent demands on the energy density and safety of rechargeable batteries. Traditional commercial lithium-ion batteries generally use flammable and volatile liquid organic electrolytes, posing significant safety hazards in the face of mechanical abuse or thermal runaway. In contrast, solid-state batteries, by using solid electrolytes instead of liquid electrolytes, fundamentally solve the problems of leakage and thermal runaway, and are therefore widely recognized as the ultimate technology for next-generation high-energy-density batteries.

[0003] Among numerous solid-state electrolyte systems, polymer solid-state electrolytes based on in-situ thermal polymerization crosslinking technology, especially those represented by polyethylene glycol diacrylate (PEG diacrylate), have become one of the most promising technologies for industrialization because their precursors can fully wet the positive and negative electrode interfaces in liquid form before polymerization, and then solidify in-situ within the battery to form a three-dimensional polymer network. This significantly improves the poor solid-solid interface contact problem commonly found in solid-state batteries. However, in-depth electrochemical mechanism studies by those skilled in the art have revealed that conventional PEG diacrylate-based in-situ crosslinked solid-state electrolytes still face extremely difficult-to-overcome technical bottlenecks at the microscopic level.

[0004] First, there is the serious problem of ether-oxygen bond binding and concentration polarization. These polymer matrices contain a high density of ether-oxygen bonds, which exhibit a strong coordination binding effect on lithium ions during charge and discharge, forming a dense solvation sheath. When the lithium salt dissociates, the large anions are almost unbound in the polymer network, and their movement speed is much greater than that of the tightly bound lithium ions, resulting in a very low room temperature lithium ion transference number in conventional polymer electrolytes. This anion-dominated transport mechanism can cause extremely severe concentration polarization during high-current charge and discharge, which not only greatly limits the fast-charging performance of the battery, but also induces an imbalance in the local space charge layer on the negative electrode surface, thereby accelerating the nucleation and growth of lithium dendrites, which can easily puncture the polymer network and cause a short circuit in the battery.

[0005] Secondly, to improve room temperature ionic conductivity, existing technologies typically add conventional nitrile plasticizers such as succinic anionizers or inorganic fast ion conductor fillers such as nano-sized lithium lanthanum zirconium oxide to polymer precursors. However, conventional succinic anionizers lack strong electron-withdrawing groups and cannot restrict the free movement of anions. Furthermore, they are easily oxidized and decomposed under high voltage, making them completely unsuitable for high-energy-density cathodes such as high-nickel ternary cathodes. At the same time, during the phase transition from liquid precursor to solid-state network dynamic crosslinking, nano-sized inorganic fillers are prone to severe agglomeration in the polymer matrix due to their extremely high surface energy. Ordinary polymer segments cannot form an effective wetting layer on the surface of inorganic particles, resulting in huge microscopic interfacial resistance between the inorganic and organic phases, making it impossible to form continuous lithium-ion permeation channels.

[0006] In summary, there is an urgent need in this field for a novel composite solid electrolyte system that can simultaneously break the binding of lithium ions to ether oxygen bonds at the molecular level during in-situ crosslinking to target and anchor large anions and reshape the solvation sheath, while maintaining extremely high antioxidant stability under high voltage and constructing a robust solid electrolyte interface film in situ. It also needs to be able to fully wet and anchor inorganic fillers in situ to completely open up the ion transport channels at the microscopic interface. Summary of the Invention

[0007] This invention overcomes the shortcomings of the prior art and provides a solid-state battery electrolyte containing nitrile fluoride additives and its preparation method.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is: a solid-state battery electrolyte containing nitrile fluoride additives, comprising:

[0009] The three-dimensional polymer network matrix formed by in-situ polymerization and crosslinking of polyethylene glycol diacrylate, inorganic fast ion conductor filler, double lithium salt system, 2,2-difluoromalononitrile and fluoroethylene carbonate;

[0010] The inorganic fast ion conductor filler is a nano-sized lithium lanthanum zirconium oxide;

[0011] The dual lithium salt system consists of lithium bis(trifluoromethanesulfonylimide) and lithium difluorooxalateborate.

[0012] The ratio of the total molar number of cyano groups in the 2,2-difluoromalononitrile to the total molar number of lithium ions in the bis-lithium salt system is from 0.15:1 to 0.4:1.

[0013] The mass ratio of the 2,2-difluoromalononitrile to the nano-sized lithium lanthanum zirconium oxide is 1:4 to 1:8.

[0014] The fluoroethylene carbonate accounts for 1% to 3% of the total mass of the solid-state battery electrolyte containing the nitrile fluoride additive.

[0015] In a preferred embodiment of the present invention, the average particle size of the nanoscale lithium lanthanum zirconium oxide is 50 nm to 200 nm.

[0016] In a preferred embodiment of the present invention, the number average molecular weight of the polyethylene glycol diacrylate forming the three-dimensional polymer network matrix is ​​400 to 1000.

[0017] In a preferred embodiment of the present invention, the molar ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalateborate is 8:2 to 9:1.

[0018] In a preferred embodiment of the present invention, the polyethylene glycol diacrylate forming the three-dimensional polymer network matrix is ​​100 parts by mass, the bis-lithium salt system is 40 to 50 parts by mass, the 2,2-difluoromalononitrile is 1 to 3.5 parts by mass, and the nano-sized lithium lanthanum zirconium oxide is 6 to 20 parts by mass, and the actual values ​​of each component strictly satisfy the molar ratio and mass ratio relationship described in claim 1.

[0019] In a preferred embodiment of the present invention, the thickness of the solid-state battery electrolyte containing nitrile fluoride additives is 20 micrometers to 50 micrometers.

[0020] A method for preparing a solid-state battery electrolyte containing nitrile fluoride additives includes the following steps:

[0021] S1. 2,2-Dibromomalononitrile and potassium fluoride are reacted at 80°C to 150°C in the presence of 1-butyl-3-methylimidazolium tetrafluoroborate and then separated by distillation to obtain 2,2-difluoromalononitrile with a purity greater than 99.8%.

[0022] S2. Mix polyethylene glycol diacrylate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, nano-sized lithium lanthanum zirconium oxide, 2,2-difluoromalononitrile obtained in the first step, fluoroethylene carbonate, and thermal initiator in a predetermined proportion to form a liquid precursor.

[0023] S3. The liquid precursor is subjected to in-situ thermal polymerization and cross-linking at 50°C to 80°C to obtain the solid battery electrolyte containing nitrile fluoride additives.

[0024] In a preferred embodiment of the present invention, in step S1, the 2,2-dibromomalononitrile is 1 part by mass, the potassium fluoride is 1.0 to 1.5 parts, and the 1-butyl-3-methylimidazolium tetrafluoroborate is 30 to 300 parts.

[0025] In a preferred embodiment of the present invention, in step S2, the thermal initiator is azobisisobutyronitrile.

[0026] In a preferred embodiment of the present invention, in step S3, the in-situ thermal polymerization crosslinking molding time is 12 hours to 24 hours.

[0027] This invention addresses the shortcomings of the prior art and has the following beneficial effects:

[0028] This invention restricts the molar ratio of cyano groups in 2,2-difluoromalononitrile to lithium ions in the double lithium salt to a microscopic range of 0.15:1 to 0.4:1 in a solid polymer network. The 2,2-difluoromalononitrile molecule forms an extremely electron-deficient center due to the strong electron-withdrawing effect of fluorine atoms. This center can generate a strong dipole interaction with the large anions in the double lithium salt (such as the lithium bis(trifluoromethanesulfonyl)imide anion) and firmly anchor them. At the same time, the appropriate coordination of its terminal cyano group strongly weakens the original binding of lithium ions to the ether oxygen bond in the polyethylene glycol diacrylate matrix. This microscopic mechanism of targeted reshaping of the solvation sheath greatly releases free lithium ions, resulting in a cliff-like leap in the lithium ion transport number of the composite system at room temperature. Traditional polymer solid electrolytes are often subject to extremely serious concentration polarization problems due to the high-speed ionization of anions and the slow transport of lithium ions. This invention completely breaks through this constraint at the molecular thermodynamic level. It not only eliminates the polarization phenomenon caused by the aggregation of free anions during high-current charging and discharging, but also inhibits the nucleation and growth of lithium dendrites induced by the imbalance of space charge layer from the source, providing a solid guarantee for the high safety and fast charging of solid-state batteries.

[0029] The solid-state battery electrolyte of this invention is a three-dimensional network matrix formed by in-situ polymerization and crosslinking of polyethylene glycol diacrylate in the presence of 2,2-difluoromalononitrile. During the crosslinking process of dynamic phase transition from liquid precursor to solid network, 2,2-difluoromalononitrile, with its special molecular spatial configuration, forcibly inserts itself between polymer chains undergoing free radical polymerization like a microscopic wedge, triggering a strong steric hindrance effect. This disrupts the original regular arrangement tendency of the polymer matrix, significantly reduces the intrinsic crystallinity of the solid-state electrolyte, and promotes a rapid expansion of the amorphous region area. Compared with conventional linear nitrile plasticizers, which often remain free in the pores after polymerization, are prone to phase separation, and cannot fundamentally change the crystalline thermodynamic state of the matrix, this in-situ structural reshaping of the invention not only maintains the excellent macroscopic mechanical strength of the composite system, but also constructs a wide and continuous transport channel for lithium ions at the microscopic scale. This endows the solid-state electrolyte with ultra-high room temperature ionic conductivity comparable to that of liquid systems, removing the performance barrier for efficient operation of solid-state batteries at room temperature.

[0030] This invention precisely locks the mass ratio of 2,2-difluoromalononitrile to nano-scale lithium lanthanum zirconium oxide inorganic fast ion conductor filler within the critical range of 1:4 to 1:8, and introduces a specific amount of fluoroethylene carbonate to work together. This invention allows 2,2-difluoromalononitrile, which has an extremely strong dipole moment, to form a perfect monomolecular wetting layer on the surface of nano-inorganic particles with extremely high surface energy. This not only eliminates the tendency of particle aggregation through intermolecular forces, but also promotes the preferential electrochemical reduction and oxidation of the inorganic filler on the positive and negative electrode surfaces by the ultra-low highest occupied molecular orbital energy level endowed by the strong electron-withdrawing groups inside the molecule. This results in the inorganic filler being anchored extremely uniformly in the organic cross-linked network, while simultaneously constructing a dense and robust passivation layer rich in lithium fluoride in situ on the electrode surface. Compared to conventional organic-inorganic composite solid electrolytes, which are long plagued by the huge solid-solid interfacial impedance caused by the agglomeration of inorganic particles and the problem that the polymer matrix is ​​prone to irreversible oxidative decomposition above 4.0V, this invention, through the monomolecular-level wetting of the inorganic phase interface by additives and the dual film-forming protection of the electrode interface, not only completely opens up the lithium-ion permeation channel at the organic-inorganic phase interface to achieve a sharp drop in interfacial impedance, but also successfully widens the electrochemical stability window of the system to above 4.5V, establishing an indestructible moat for the safe application of high-energy-density cathodes such as high-nickel ternary cathodes in solid-state batteries. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a flowchart of a method for preparing a solid-state battery electrolyte containing nitrile fluoride additives according to the present invention. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0035] The embodiments of this invention are applicable to the preparation of an in-situ thermally polymerized crosslinked composite solid-state battery electrolyte for high-energy-density secondary lithium batteries. This invention abandons the conventional approach of using a single film-forming additive or physical blending, and creatively introduces 2,2-difluoromalononitrile, which has a strong electron-deficient center and specific steric hindrance. By strictly locking the molar ratio of the cyano group in this specific molecule to the lithium ion in the double lithium salt system between 0.15:1 and 0.4:1, and simultaneously locking the mass ratio of this molecule to the nano-scale lithium lanthanum zirconium oxide filler between 1:4 and 1:8, during the in-situ thermally polymerized crosslinking process of polyethylene glycol diacrylate, the synergistic mutation effect of the micro-proportion is utilized to simultaneously achieve targeted reshaping of the solvation sheath, strong steric hindrance to reduce crystallinity, and single-molecule-level wetting and dual film formation at the interface, thereby completely overcoming the bottlenecks of low room temperature conductivity, easy oxidation under high voltage, and easy agglomeration of fillers in traditional polymer solid-state batteries.

[0036] Traceability of experimental materials and preparation of self-made materials:

[0037] Polyethylene glycol diacrylate (PEGDA): Product number P131592, Mn=600, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0038] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI): Product No. B398978, purity ≥99.9%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0039] Lithium difluorooxalate borate (LiDFOB): Product No. L303675, purity ≥99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0040] Fluorinated ethylene carbonate (FEC): Product No. F1491912, purity ≥99.5%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0041] Precursor materials for preparing nanoscale lithium lanthanum zirconium oxide (LLZTO):

[0042] Lithium nitrate: Product number L100136, purity ≥99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] Lanthanum nitrate hexahydrate: Product No. L106046, purity ≥99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] Zirconium oxynitrate hydrate: Product No. Z104396, purity ≥99.5%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0045] Tantalum pentachloride: Product number T301576, purity ≥99.8%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0046] Citric acid monohydrate: Product number C598654, purity ≥99.5%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0047] Anhydrous ethanol: National Drug Code 10009218, purity ≥99.7%, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0048] Ammonia water: National Drug Code XW011336216024, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0049] Synthetic raw materials for preparing 2,2-difluoromalononitrile:

[0050] Azobisisobutyronitrile (AIBN): Product No. A104255, purity ≥98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0051] 2,2-Dibromomalononitrile: Product No. BD01329347, purity 98%, purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd.;

[0052] Anhydrous potassium fluoride (KF): Product number P116293, purity ≥99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0053] 1-Butyl-3-methylimidazolium tetrafluoroborate: Product No. B359377, purity ≥98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0054] Battery assembly components: Commercial NCM811 aluminum foil positive electrode sheet with single-sided coating, 50-micron thick lithium metal foil, and CR2032 button battery casing and other auxiliary components are purchased from conventional battery material suppliers.

[0055] Preparation of homemade materials:

[0056] 1) Preparation of nano-sized lithium lanthanum zirconium oxide (LLZTO) powder:

[0057] The nanoscale inorganic fast ion conductor filler (chemical formula Li) used in the embodiments of this invention 6.4 La3Zr 1.4 Ta 0.6 O 12 The sol-gel method was used for pre-synthesis, and the specific steps and determined process parameters are as follows:

[0058] According to the stoichiometric ratio, the required molar amounts of lanthanum nitrate hexahydrate, zirconium oxynitrate hydrate, and tantalum pentachloride are added to an appropriate amount of anhydrous ethanol and dissolved completely under magnetic stirring.

[0059] To compensate for lithium volatilization during the high-temperature calcination process, lithium nitrate was added in excess at a stoichiometric ratio of 10%, and the mixture was stirred until a transparent solution was formed.

[0060] According to the ratio of total molar amount of metal ions to molar amount of citric acid of 1:2, add citric acid monohydrate as a complexing agent, add ammonia water dropwise to adjust the pH value of the solution to 8, and stir in a constant temperature water bath at 80°C for 4 hours until a viscous wet gel is formed.

[0061] The wet gel was transferred to a vacuum oven at 120°C and dried for 12 hours to obtain the dry gel precursor.

[0062] The dry gel was placed in an alumina crucible and heated to 400°C at a heating rate of 2°C / min in air atmosphere and held for 2 hours to remove organic matter. Then the temperature was increased to 900°C and calcined at a constant temperature for 6 hours.

[0063] After the calcined product is cooled, it is placed in a zirconia ball mill jar and subjected to high-energy wet ball milling at a speed of 400 rpm for 12 hours using isopropanol as the ball milling medium.

[0064] After centrifugation and vacuum drying at 80°C, the ground product yields high-purity lithium lanthanum zirconium oxide powder with an average particle size of approximately 100 nm for later use.

[0065] 2) Preparation of the specific additive (2,2-difluoromalononitrile):

[0066] Under the protection of high-purity argon gas with water and oxygen content both below 0.1 ppm, 100 g of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, 10 g of 2,2-dibromomalononitrile and 12 g of anhydrous potassium fluoride were added sequentially to the reaction vessel and mixed thoroughly.

[0067] The reaction system was heated to 120°C and stirred at a constant temperature for 6 hours.

[0068] After the reaction was completed, the product was separated by distillation, and specific fractions were collected. Finally, a colorless liquid of 2,2-difluoromalononitrile with a purity greater than 99.8% as determined by gas chromatography was obtained. The liquid was sealed and stored in the dark for later use.

[0069] like Figure 1 As shown, a method for preparing a solid-state battery electrolyte containing nitrile fluoride additives includes the following steps:

[0070] S1. 2,2-Dibromomalononitrile and potassium fluoride are reacted at 80°C to 150°C in the presence of 1-butyl-3-methylimidazolium tetrafluoroborate and then separated by distillation to obtain 2,2-difluoromalononitrile with a purity greater than 99.8%.

[0071] S2. Mix polyethylene glycol diacrylate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, nano-sized lithium lanthanum zirconium oxide, 2,2-difluoromalononitrile obtained in the first step, fluoroethylene carbonate, and thermal initiator in a predetermined proportion to form a liquid precursor.

[0072] S3. The liquid precursor is subjected to in-situ thermal polymerization and cross-linking at 50°C to 80°C to obtain the solid battery electrolyte containing nitrile fluoride additives.

[0073] Each step will be explained in detail below:

[0074] The core of step S1 lies in obtaining key small molecule additives with strong electron-withdrawing and electron-deficient centers.

[0075] Specifically, 1-butyl-3-methylimidazolium tetrafluoroborate was used as the reaction medium and phase transfer catalyst to drive a specific fluorination reaction between 2,2-dibromomalononitrile and potassium fluoride.

[0076] The reaction temperature here must be strictly controlled within the range of 80℃ to 150℃. If the temperature is below 80℃, the activation energy of the fluorination reaction is insufficient, which will result in a very low conversion rate. If the temperature is above 150℃, it is very easy to trigger side reactions such as excessive cracking or carbonization of the reactants.

[0077] After the reaction is completed, the purity of the final 2,2-difluoromalononitrile is ensured to be greater than 99.8% by distillation separation. This extremely high purity threshold prevents residual bromide ions or water from causing irreversible electrochemical side reactions in subsequent high-voltage battery cycles.

[0078] Step S2 aims to achieve a perfect microscopic mixing of polymer monomers, inorganic fillers, and specific additives in the liquid phase.

[0079] Specifically, polyethylene glycol diacrylate, a double lithium salt system composed of lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalate borate (the molar ratio of the two needs to be controlled between 8:2 and 9:1), nano-sized lithium lanthanum zirconium oxide, the above-prepared 2,2-difluoromalononitrile, fluoroethylene carbonate accounting for 1% to 3% of the total mass of the system, and thermal initiators such as azobisisobutyronitrile are thoroughly stirred and dispersed.

[0080] During this process, it is essential to ensure that the feeding ratio strictly meets the microscopic boundary conditions defined in this invention: that is, the ratio of the total molar number of cyano groups in 2,2-difluoromalononitrile to the total molar number of lithium ions is 0.15:1 to 0.4:1, and the mass ratio of 2,2-difluoromalononitrile to nano-sized lithium lanthanum zirconium oxide is 1:4 to 1:8.

[0081] The liquid precursor of this invention, which falls entirely within the aforementioned quantitative range, provides a precise material basis for solvated sheath remodeling and filler interface monomolecular wetting during the subsequent crosslinking process, while ensuring fluidity and wettability.

[0082] In step S3, the prepared liquid precursor is injected into the battery and fully wets the positive and negative electrode interfaces, and then placed in a heating environment to initiate free radical polymerization.

[0083] The polymerization and curing temperature is set between 50°C and 80°C, and the temperature is maintained for 12 to 24 hours.

[0084] If the curing temperature is below 50℃ or the time is less than 12 hours, the thermal initiator will decompose slowly, which will lead to insufficient cross-linking of the precursor. The large amount of unreacted liquid phase remaining inside will cause a sharp decrease in the macroscopic mechanical strength of the electrolyte.

[0085] Conversely, if the temperature exceeds 80℃ or the holding time exceeds 24 hours, the excess heat energy can easily induce gas generation inside the electrolyte, damaging the solid electrolyte interphase (SEI) film that has already been formed in situ. Only through gentle cross-linking within this time and temperature range can 2,2-difluoromalononitrile perfectly exert its steric hindrance effect, deeply disrupting the regular crystallization of polymer chains, and ultimately solidifying to form a dense, uniform composite solid-state battery electrolyte with a three-dimensional interpenetrating network structure.

[0086] Example 1:

[0087] S1. 10g of 2,2-dibromomalononitrile and 12g of potassium fluoride were reacted at 120℃ for 6 hours in the presence of 100g of 1-butyl-3-methylimidazolium tetrafluoroborate and then separated by distillation to obtain 2,2-difluoromalononitrile with a purity greater than 99.8%.

[0088] S2. Mix 100.0g of polyethylene glycol diacrylate, 36.75g of lithium bis(trifluoromethanesulfonyl)imide, 3.25g of lithium difluorooxalate borate, 11.52g of nano-sized lithium lanthanum zirconium oxide, 1.92g of 2,2-difluoromalonium obtained in step S1, 2.0g of fluoroethylene carbonate, and 0.5g of azobisisobutyronitrile evenly and stir continuously at room temperature for 12 hours to form a transparent and homogeneous liquid precursor.

[0089] S3. The liquid precursor is injected into a battery casing equipped with positive and negative electrodes, and in-situ thermal polymerization and cross-linking are carried out at 60°C for 18 hours to obtain the solid battery electrolyte containing nitrile fluoride additives.

[0090] Example 2:

[0091] The preparation method in this embodiment is basically the same as that in Example 1, with the only difference being:

[0092] In step S2, 1.15 g of 2,2-difluoromalononitrile and 6.90 g of nano-sized lithium lanthanum zirconium oxide were added.

[0093] Example 3:

[0094] The preparation method in this embodiment is basically the same as that in Example 1, with the only difference being:

[0095] In step S2, 3.07 g of 2,2-difluoromalononitrile and 18.42 g of nano-sized lithium lanthanum zirconium oxide were added.

[0096] Comparative Example 1:

[0097] The preparation method of this comparative example is basically the same as that of Example 1, with the only difference being:

[0098] In step S2, 1.08 g of 2,2-difluoromalononitrile and 6.48 g of nano-sized lithium lanthanum zirconium oxide were added.

[0099] Comparative Example 2:

[0100] The preparation method of this comparative example is basically the same as that of Example 1, with the only difference being:

[0101] In step S2, 3.15 g of 2,2-difluoromalononitrile and 18.90 g of nano-sized lithium lanthanum zirconium oxide were added.

[0102] Example 4:

[0103] The preparation method in this embodiment is basically the same as that in Example 1, with the only difference being:

[0104] In step S2, the amount of 2,2-difluoromalononitrile remains unchanged at 1.92 g, while the amount of nano-sized lithium lanthanum zirconium oxide added is adjusted to 15.36 g.

[0105] Example 5:

[0106] The preparation method in this embodiment is basically the same as that in Example 1, with the only difference being:

[0107] In step S2, the amount of 2,2-difluoromalononitrile remains unchanged at 1.92 g, while the amount of nano-sized lithium lanthanum zirconium oxide added is adjusted to 7.68 g.

[0108] Comparative Example 3:

[0109] The preparation method of this comparative example is basically the same as that of Example 1, with the only difference being:

[0110] In step S2, the amount of 2,2-difluoromalononitrile remains unchanged at 1.92 g, while the amount of nano-sized lithium lanthanum zirconium oxide added is slightly adjusted to 16.32 g.

[0111] Comparative Example 4:

[0112] The preparation method of this comparative example is basically the same as that of Example 1, with the only difference being:

[0113] In step S2, the amount of 2,2-difluoromalononitrile remains unchanged at 1.92 g, while the amount of nano-sized lithium lanthanum zirconium oxide added is slightly adjusted to 6.72 g.

[0114] Comparative Example 5:

[0115] The preparation method of this comparative example is basically the same as that of Example 1, the only difference being the replacement of the core additive:

[0116] Step S1 is omitted;

[0117] In step S2, instead of adding 2,2-difluoromalononitrile, it is replaced with an equimolar amount of conventional succinate, which is 1.51 g; the amount of nano-sized lithium lanthanum zirconium oxide remains unchanged at 11.52 g.

[0118] Example 6:

[0119] The preparation method of this embodiment is basically the same as that of Example 1, except that in step S2, the amount of fluoroethylene carbonate (FEC) added is adjusted to 1.56g.

[0120] Example 7:

[0121] The preparation method of this embodiment is basically the same as that of Example 1, except that in step S2, the amount of fluoroethylene carbonate (FEC) added is adjusted to 4.76g.

[0122] Comparative Example 6:

[0123] The preparation method of this comparative example is basically the same as that of Example 1, except that fluoroethylene carbonate (FEC) is not added in step S2.

[0124] Comparative Example 7:

[0125] The preparation method of this comparative example is basically the same as that of Example 1, except that in step S2, the amount of fluoroethylene carbonate (FEC) added is adjusted to 8.10g.

[0126] The electrolytes obtained in the above embodiments and comparative examples were subjected to performance testing. The testing methods included:

[0127] Lithium-ion transference number (LTL) Tests and calculations for )

[0128] In a glove box filled with high-purity argon, the prepared liquid precursors were dropped between two symmetrical lithium metal foils, and the button cell was assembled and sealed. Then, in-situ thermal polymerization and crosslinking were carried out at 60°C for 18 hours to produce Li|solid electrolyte|Li symmetrical button cell.

[0129] Under a constant temperature environment of 25℃, the classic Bruce-Vincent polarization method was used in the electrochemical workstation for testing. First, the initial impedance (R0) of the bulk phase and interface before polarization was measured by AC impedance spectroscopy. Then, a constant small DC bias voltage (ΔV=10mV) was applied for chronoamperometry polarization, and the initial current (I0) and the steady-state current (I0) after polarization reached a steady state were recorded. ss Finally, the steady-state impedance (R) after polarization was tested again. ss ).

[0130] The lithium-ion transference number is calculated using the following formula:

[0131] .

[0132] Critical current density (CCD) testing:

[0133] The above-mentioned Li|solid electrolyte|Li symmetric battery was placed in a battery testing system at 25°C for stepped constant current charge-discharge cycle.

[0134] The test procedure was set to: initial current density of 0.1 mA / cm². 2 Each charge-discharge half-cycle lasted 1 hour, followed by a charge-discharge cycle at 0.1 mA / cm. 2 The amplitude of the current density increases progressively.

[0135] By continuously monitoring the voltage response curves at both ends of the battery, when the voltage curve suddenly drops sharply (indicating that lithium dendrites pierce the electrolyte, causing an internal micro-short circuit), the maximum current density that the previous step can withstand is recorded as the critical current density of the solid electrolyte.

[0136] 500-hour cyclic interfacial impedance growth rate (ΔR) int Test of )

[0137] Using the aforementioned Li|solid electrolyte|Li symmetric cell, the initial solid-solid interface impedance (Ri) before cycling was first determined by electrochemical impedance spectroscopy (EIS) at 25°C. int,0 );

[0138] Subsequently, at 0.5 mA / cm 2 At a fixed current density, a single charge-discharge time of 1 hour was set, and a continuous constant current deposition / stripping cycle test was conducted for up to 500 hours.

[0139] After the cycle is completed, the final-state interfacial impedance (Ri) is measured again using EIS. int,500 );

[0140] The impedance growth rate is calculated using the following formula:

[0141] .

[0142] Precursor droplet dynamic contact angle test:

[0143] The nanoscale lithium lanthanum zirconium oxide powder used in the examples and comparative examples was pressed into dense ceramic targets under a pressure of 200 MPa. At room temperature, using a contact angle meter, the prepared liquid precursors (clear liquid without fillers) were dropped onto the surface of the LLZTO ceramic targets, and the static contact angle at 5 seconds after the droplets contacted the targets was recorded. The smaller the contact angle, the stronger the synergistic effect of the precursor on the monomolecular wetting of the inorganic filler.

[0144] Apparent ionic conductivity activation energy ( )test:

[0145] The solid electrolyte, after in-situ polymerization and solidification, was assembled into an SS|solid electrolyte|SS blocking battery. The AC impedance spectrum of the system was measured every 10°C within the range of 25°C to 80°C, and the ionic conductivity at different temperatures was calculated. Fitting according to the Arrhenius formula The linear relationship with 1000 / T, the slope of which represents the apparent activation energy. The lower the value, the lower the energy barrier for lithium-ion desolvation, and the more significant the synergistic effect of reshaping the solvation sheath.

[0146] The results of the above tests are shown in Table 1:

[0147] Table 1 Electrochemical kinetics and interfacial stability test data for each experimental group

[0148] Example 1 0.68 1.35 3.20% 4° 0.25 Example 2 0.55 1.05 8.50% 8° 0.38 Example 3 0.61 0.95 11.20% 5° 0.32 Example 4 0.62 0.98 9.70% 15° 0.28 Example 5 0.65 1.15 7.40% 6° 0.27 Example 6 0.66 1.30 6.1% 5° 0.26 Example 7 0.65 1.25 5.8% 5° 0.26 Comparative Example 1 0.35 0.65 45.80% 35° 0.58 Comparative Example 2 0.58 0.45 88.40% 7° 0.35 Comparative Example 3 0.42 0.25 145.60% 52° 0.45 Comparative Example 4 0.51 0.35 124.30% 4° 0.38 Comparative Example 5 0.26 0.6 210.50% 48° 0.65 Comparative Example 6 0.67 0.85 385.2% 5° 0.25 Comparative Example 7 0.61 0.55 175.4% 6° 0.28

[0149] The apparent activation energy (#imgpt11#) is the most direct thermodynamic indicator for measuring the desolvation energy barrier of lithium ions. As shown in Table 2, Comparative Example 5, which uses conventional succinate with equimolar substitution, has an #imgpt12# as high as 0.65 eV, indicating that conventional nitriles cannot weaken the binding of the polymer network to lithium ions; while the #imgpt13# of Example 1 drops sharply to an excellent 0.25 eV, and the lithium ion transference number jumps to 0.68. This essential leap in thermodynamic parameters directly and uniquely proves the synergistic mechanism between the features described in this invention: that is, by strictly locking the molar ratio (0.15:1 to 0.4:1) of 2,2-difluoromalononitrile, relying on the extremely electron-deficient cyano group excited by its fluorine atom, it successfully anchors the free anion at the microscopic level, forcibly breaking the original solvation sheath, and reconstructing the lithium ion transport channel from the bottom layer.

[0150] The direct synergistic effect of the additive and inorganic filler at the monomolecular level confirms that the fundamental cause of filler agglomeration and interfacial impedance lies in the poor wettability of the precursor. Dynamic contact angle data directly confirms this physicochemical process: when the mass ratio of additive to nanofiller falls below the lower limit (1:8.5 in Comparative Example 3, with more filler), the contact angle of the precursor on the LLZTO surface reaches as high as 52°, macroscopically manifested as a catastrophic drop in its critical current density (CCD) to 0.25 mA / cm². 2 In the case of the battery, dendrites can easily cause short circuits. In contrast, in Example 1, the contact angle is only 4°, which shows near-perfect instantaneous spreading and wetting. This directly confirms that the specific micro-ratio of 1:4 to 1:8 specified in this invention can drive the additive to form a complete monomolecular wetting layer in situ on ceramic particles with extremely high surface energy, completely eliminating stress concentration and micro-agglomeration at the solid-solid interface. This is a non-obvious preferred parameter.

[0151] The synergistic confirmation of FEC content in defining the passivation film boundary, combined with data from Examples 6 and 7 and Comparative Examples 6 and 7, shows that, while ensuring optimal synergy of the core additives, the content of fluoroethylene carbonate (FEC) constitutes the final high-pressure defense line. Comparative Example 6, which contains no FEC, failed to form a robust LiF-rich SEI film at the lithium anode interface, resulting in a 500-hour interfacial impedance growth rate soaring to 385.2%. In Comparative Example 7, with an FEC overload of 5.0%, excessive flexible decomposition products led to a decrease in the mechanical strength of the polymer network, causing its CCD to plummet to 0.55 mA / cm². 2 Furthermore, it triggers severe and persistent side reactions (impedance increase of 175.4%). Only by strictly limiting FEC to the range of 1% to 3% (Examples 1, 6, 7) can an extremely stable electrode interface protective film be constructed in synergy with specific nitrile additives without compromising the mechanical strength of the in-situ crosslinked network, thus maintaining its excellent impedance growth rate at a level below 6%.

[0152] In summary, this invention abandons the traditional approach of relying on conventional plasticizers for physical viscosity reduction in polymer solid-state battery electrolytes. Instead, it creatively introduces 2,2-difluoromalononitrile with strong electron-withdrawing fluorine atoms as a specific molecular additive. By strictly controlling the molar ratio of its internal cyano group to lithium ions in the dual lithium salt system between 0.15:1 and 0.4:1, and precisely controlling its mass ratio with nano-sized lithium lanthanum zirconium oxide between 1:4 and 1:8, this invention utilizes this non-obvious microscopic synergy and critical mutation effect to perfectly achieve targeted reshaping of the solvation sheath (significantly increasing lithium-ion transport number) and monomolecular wetting of the solid-solid interface, while completely eliminating the microscopic aggregation of nano-ceramic fillers and interfacial mechanical stress. This technical solution overcomes the industry bottlenecks of traditional solid-state batteries—low room-temperature conductivity, poor critical current density, and irreversible oxidation under high voltage—from the underlying physicochemical mechanism, exhibiting extremely excellent electrochemical kinetic performance and long-term high-voltage interfacial stability.

[0153] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A solid-state battery electrolyte containing nitrile fluoride additives, characterized in that, include: The three-dimensional polymer network matrix formed by in-situ polymerization and crosslinking of polyethylene glycol diacrylate, inorganic fast ion conductor filler, double lithium salt system, 2,2-difluoromalononitrile and fluoroethylene carbonate; The inorganic fast ion conductor filler is a nano-sized lithium lanthanum zirconium oxide; The dual lithium salt system consists of lithium bis(trifluoromethanesulfonylimide) and lithium difluorooxalateborate. The ratio of the total molar number of cyano groups in the 2,2-difluoromalononitrile to the total molar number of lithium ions in the bis-lithium salt system is from 0.15:1 to 0.4:

1. The mass ratio of the 2,2-difluoromalononitrile to the nano-sized lithium lanthanum zirconium oxide is 1:4 to 1:

8. The fluoroethylene carbonate accounts for 1% to 3% of the total mass of the solid-state battery electrolyte containing the nitrile fluoride additive.

2. The solid-state battery electrolyte containing nitrile fluoride additives according to claim 1, characterized in that, The average particle size of the nanoscale lithium lanthanum zirconium oxide is 50 nm to 200 nm.

3. The solid-state battery electrolyte containing nitrile fluoride additives according to claim 1, characterized in that, The number-average molecular weight of the polyethylene glycol diacrylate forming the three-dimensional polymer network matrix is ​​between 400 and 1000.

4. A solid-state battery electrolyte containing nitrile fluoride additives according to claim 1, characterized in that, The molar ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalateborate is 8:2 to 9:

1.

5. A solid-state battery electrolyte containing nitrile fluoride additives according to claim 1, characterized in that, Based on 100 parts by mass of the polyethylene glycol diacrylate forming the three-dimensional polymer network matrix, the bis-lithium salt system comprises 40 to 50 parts by mass, the 2,2-difluoromalononitrile comprises 1 to 3.5 parts by mass, and the nano-sized lithium lanthanum zirconium oxide comprises 6 to 20 parts by mass, and the actual values ​​of each component strictly satisfy the molar ratio and mass ratio relationship described in claim 1.

6. A solid-state battery electrolyte containing nitrile fluoride additives according to claim 1, characterized in that, The thickness of the solid-state battery electrolyte containing nitrile fluoride additives is 20 micrometers to 50 micrometers.

7. A method for preparing a solid-state battery electrolyte containing nitrile fluoride additives as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. 2,2-Dibromomalononitrile and potassium fluoride are reacted at 80°C to 150°C in the presence of 1-butyl-3-methylimidazolium tetrafluoroborate and then separated by distillation to obtain 2,2-difluoromalononitrile with a purity greater than 99.8%. S2. Mix polyethylene glycol diacrylate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, nano-sized lithium lanthanum zirconium oxide, 2,2-difluoromalononitrile obtained in the first step, fluoroethylene carbonate, and thermal initiator in a predetermined proportion to form a liquid precursor. S3. The liquid precursor is subjected to in-situ thermal polymerization and cross-linking at 50°C to 80°C to obtain the solid battery electrolyte containing nitrile fluoride additives.

8. The method for preparing a solid-state battery electrolyte containing nitrile fluoride additives according to claim 7, characterized in that, In step S1, by mass parts, the 2,2-dibromomalononitrile is 1 part, the potassium fluoride is 1.0 to 1.5 parts, and the 1-butyl-3-methylimidazolium tetrafluoroborate is 30 to 300 parts.

9. The method for preparing a solid-state battery electrolyte containing nitrile fluoride additives according to claim 7, characterized in that, In step S2, the thermal initiator is azobisisobutyronitrile.

10. The method for preparing a solid-state battery electrolyte containing nitrile fluoride additives according to claim 7, characterized in that, In step S3, the in-situ thermal polymerization crosslinking molding time is 12 to 24 hours.